Kampung Kapitan Sebagai Sumber Pembelajaran IPS Terpadu - Kristian, Indah (Yayasan Sembilan Pemuda Indonesia, 2022)
The objective of this research was to explain how Kampung Kapitan became a learning resource for students in class VII. Tjoa Tiong Gie (Mulyadi) and Oey Eng Sui, key informants, and Sri Hastuti, an Integrated Social Studies teacher, participated in this study using a qualitative descriptive technique. The qualitative data from the study was evaluated. The results of the study indicate that Kapitan Village might be used as an Integrated Social Studies learning resource with Basic Competence 4.1.